The Concept of Nusyuz in Husband Wife Relations From an Islamic Legal Perspective (Case Study in Banabungi Village, South Button District) - Irma Purnamayanti; La Hanudin; Wa Ode Sela Safira (AIQU: Journal Multidiscipliner of Science, 2023)
This research is an Islamic Law Review of the Concept of Nusyuz in Husband and Wife Relations in Banabungi Village, South Buton Regency. The main points of discussion are: a) The concept of Nusyuz in the Islamic Law Perspective in Banabungi Village, South Buton Regency and b) Husband and Wife Relations from the Islamic Law Perspective in Banabungi Village, South Buton Regency. This research uses qualitative research methods, sampling uses non-random sampling/non-probability sampling subjects, the research instrument uses a qualitative approach and the data collection used is observation, interviews and documentation and the data analysis technique used has three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research show that: a) Determining Nusyuz in Banabungi Village is based on the forms of violations committed by the husband/wife during marriage. b) Review of Islamic Law regarding Husband and Wife Relations in Banabungi Village, namely a harmonious family is a family that is balanced and related between husband and wife. And the ideal family according to Islam is the concept of equal partnerships or equal relationships.